A composite proton exchange membrane and its preparation method and application
By introducing sulfonated ZIF-derived porous carbon materials and sulfonated carbon nanotubes into the SPEEK proton exchange membrane, the problems of high methanol permeability, high swelling rate and low proton conductivity are solved, and efficient proton conductivity and mechanical stability are achieved , overcomes the instability of ZIF materials under acidic conditions and is suitable for fuel cell applications.
Patent Information
- Application Number
- CN202210602184.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-30
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-05-30
AI Technical Summary
The existing SPEEK proton exchange membranes have problems such as high methanol permeability, high swelling rate and low proton conductivity, and the ZIF material is unstable under acidic conditions, which limits its application in proton exchange membranes.
采用磺化ZIF衍生多孔碳材料和磺化碳纳米管作为填充剂,结合磺化聚醚醚酮作为基质,通过特定的制备方法制备复合质子交换膜,优化其质子传导率和机械稳定性。
A composite proton exchange membrane with low methanol permeability, low swelling rate and high proton conductivity is achieved, which overcomes the instability of ZIF materials in an acidic environment, reduces production costs, and is suitable for industrial production.
Smart Images

Figure CN114865033B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fuel cells, and in particular relates to a composite proton exchange membrane and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cell (PEMFC) is an efficient and green energy conversion device with the advantages of high energy efficiency, low operating temperature, clean and pollution-free. Compared with traditional thermal power plants, proton exchange membrane fuel cells can directly convert the chemical energy of fuel into electrical energy without being restricted by the Carnot cycle. Its theoretical energy conversion rate can reach 80%, and it has great application potential in the energy field. Proton exchange membrane fuel cells are usually composed of three basic components: bipolar plates, gas diffusion layers and proton exchange membranes (PEM). During the operation of the battery, the fuel is transported to the anode for oxidation reaction, the generated protons are transmitted to the cathode through the proton exchange membrane, and the lost electrons reach the cathode through the external circuit, thereby continuously generating electrical energy. As one of the core components of PEMFC, the proton exchange membrane bears the important responsibility of transmitting protons, blocking fuel penetration, and isolating electron transfer in the fuel cell, and plays a decisive role in the performance and service life of the battery. Excellent proton exchange membranes need to have high proton conductivity, good thermal stability and mechanical properties, and excellent fuel permeation barrier properties. They also need to be cheap and have a simple preparation process to facilitate large-scale production and application. Currently, the commercial proton exchange membrane is a perfluorosulfonic acid membrane, which has good proton conductivity and chemical stability, but is expensive, has a complex production process, and has serious fuel permeability problems, which seriously hinders the commercial application of PEMFC. Therefore, it is of great significance to develop a proton exchange membrane with low cost and high performance to replace the perfluorosulfonic acid membrane.
[0003] Sulfonated polyetheretherketone (SPEEK) is a polymer with a main chain composed of rigid benzene rings and ether bonds and side chains with sulfonic acid groups. This special structure gives the material good mechanical and thermal stability, while the side chain sulfonic acid groups give the material excellent proton conductivity. Compared with perfluorosulfonic acid membranes, SPEEK has the advantages of low production cost, simple production process, fluorine-free production process, green and pollution-free, and low fuel permeability, and has great application potential in the field of proton exchange membranes. However, the proton conductivity characteristics of SPEEK are affected by the degree of sulfonation (DS) (50% ≤ DS ≤ 80%). In fact, a higher degree of sulfonation (DS) can enhance the density of acid sites and promote proton transport, but at the same time it will lead to a decrease in the mechanical and chemical stability of the proton exchange membrane, thereby affecting the performance and service life of the proton exchange membrane battery. In order to coordinate the relationship between the degree of sulfonation and performance, introducing inorganic materials into SPEEK materials is a feasible strategy. Existing SPEEK membrane filler inorganic materials, such as carbon nanotubes (CNTs), nano-silica (SiO2), graphene oxide (GO) and metal organic framework materials (MOF), can significantly reduce the membrane swelling rate and fuel permeability, and improve the mechanical strength and chemical stability of the SPEEK membrane, thereby improving the comprehensive performance of the SPEEK-based ion exchange membrane.
[0004] Carbon nanotubes (CNTs) are one-dimensional nanomaterials with a special structure of hexagonal atomic arrangement (radial size is nanometers, axial size is micrometers, and both ends of the tube are basically sealed). It is light in weight, has a perfect hexagonal structure, and has many excellent mechanical, electrical and chemical properties, which makes CNTs have broad application prospects in many fields. In the reported literature, sulfonation of CNTs by chemical modification has been widely used as PEM fillers. Recent studies have shown that the introduction of chemically modified CNTs into polymer membranes can significantly improve the mechanical stability and proton conductivity of the composite membrane, while reducing the methanol permeability. The unique tubular structure of carbon nanotubes, when filled into the proton exchange membrane, plays a role as a skeleton support, which can greatly enhance the mechanical properties of the composite membrane. At the same time, the sulfonated modified CNTs uniformly distributed in the membrane construct additional proton transmission channels in the membrane, thereby improving the proton conductivity of the composite membrane. The filling of this inorganic material can also effectively block the methanol permeation channel, thereby reducing the methanol permeability of the composite membrane. It can be seen that sulfonated CNTs are an ideal filler for proton exchange membrane filling and modification.
[0005] Metal organic framework (MOF) is a new type of material formed by the self-assembly of central metal ions and organic ligands, which has the characteristics of adjustable structure, high porosity, large specific surface area and convenient functionalization. Zeolite imidazolate framework (ZIFs) with imidazolate rings coordinated with tetrahedral divalent metal cations are used as fillers in composite polymer electrolyte membranes due to their properties in proton transfer. However, MOFs used as proton exchange membrane fillers reported in the prior art are usually MOF materials that can exist stably in acidic environments, while some other MOFs (such as zinc-based ZIF materials) are difficult to use in proton exchange membranes due to their poor stability in acidic environments, which greatly limits the application of such ZIF materials in proton exchange membranes. Therefore, while taking advantage of the high specific surface area and easy functionalization of ZIF materials, solving the problem of instability under acidic conditions is very critical for the application of ZIF materials in the field of composite proton exchange membranes. In view of the technical problems of high methanol permeability, high swelling rate and low proton conductivity of SPEEK proton exchange membrane in the existing technology, and the unstable characteristics of ZIF materials under acidic conditions limit their application in proton exchange membranes, it is necessary to develop a new proton exchange membrane. Summary of the invention
[0006] In order to overcome the problems of high methanol permeability, high swelling rate and low proton conductivity of SPEEK proton exchange membrane in the prior art, and instability of ZIF materials under acidic conditions, one of the objects of the present invention is to provide a proton exchange membrane with low methanol permeability, low swelling rate and high proton conductivity; the second object of the present invention is to provide a method for preparing such a proton exchange membrane; the third object of the present invention is to provide applications of such a proton exchange membrane.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A first aspect of the present invention provides a composite proton exchange membrane, which comprises a matrix and a filler; the matrix comprises sulfonated polyetheretherketone; and the filler comprises a sulfonated ZIF-derived porous carbon material and a sulfonated carbon nanotube.
[0009] Preferably, the mass ratio of the sulfonated polyetheretherketone, the sulfonated ZIF-derived porous carbon material and the sulfonated carbon nanotube is (20-35):1:(0.1-3); further preferably, the mass ratio of the sulfonated polyetheretherketone, the sulfonated ZIF-derived porous carbon material and the sulfonated carbon nanotube is (30-32):1:(0.1-2).
[0010] Preferably, the sulfonated polyetheretherketone contains a repeating unit as shown in formula (I);
[0011]
[0012] In formula (I), x is selected from a positive integer of 5-50, y is selected from a positive integer of 20-60, and y / x is selected from 0.8-5; further preferably, in formula (I), x is selected from a positive integer of 10-40, y is selected from a positive integer of 30-50, and y / x is selected from 1-4.
[0013] Preferably, the sulfonation degree of the sulfonated polyetheretherketone is 50%-80%.
[0014] Preferably, the sulfonated ZIF-derived porous carbon material is prepared by a preparation method comprising the following steps:
[0015] 1) mixing dimethylimidazole and zinc salt, reacting to obtain a zinc-based ZIF material;
[0016] 2) calcining the zinc-based ZIF material in an inert atmosphere or under vacuum to obtain a ZIF-derived porous carbon material;
[0017] 3) mixing the ZIF-derived porous carbon material with a mercapto-containing silane coupling agent to obtain a mercaptosilane-grafted ZIF-derived porous carbon material;
[0018] 4) Oxidizing the mercaptosilane-grafted ZIF-derived porous carbon material to obtain the sulfonated ZIF-derived porous carbon material.
[0019] Preferably, in the step 3), the mass ratio of the ZIF-derived porous carbon material to the mercapto-containing silane coupling agent is 1:(10-30); further preferably, in the step 3), the mass ratio of the ZIF-derived porous carbon material to the mercapto-containing silane coupling agent is 1:(12-20).
[0020] Preferably, the particle size of the sulfonated ZIF-derived porous carbon material is 70nm-220nm; further preferably, the particle size of the sulfonated ZIF-derived porous carbon material is 80nm-200nm.
[0021] Preferably, in step 1), the molar ratio of dimethylimidazole to zinc salt is (5-12):1; further preferably, in step 1), the molar ratio of dimethylimidazole to zinc salt is (6-10):1.
[0022] Preferably, the zinc salt includes at least one of zinc nitrate, zinc acetate and zinc chloride; further preferably, the zinc salt is zinc nitrate.
[0023] Preferably, the calcination temperature is 800°C-1000°C.
[0024] Preferably, the calcination time is 2h-4h.
[0025] Preferably, the sulfonated carbon nanotubes are prepared by a preparation method comprising the following steps:
[0026] 1) oxidizing the carbon nanotubes to obtain carboxylated carbon nanotubes;
[0027] 2) mixing the carboxylated carbon nanotubes with a mercapto-containing silane coupling agent to obtain mercaptosilane-grafted carbon nanotubes;
[0028] 3) Oxidizing the carbon nanotubes grafted with mercaptosilane to obtain the sulfonated carbon nanotubes.
[0029] Preferably, in step 2), the mass ratio of carboxylated carbon nanotubes to mercapto-containing silane coupling agent is 1:(5-25); further preferably, in step 2), the mass ratio of carboxylated carbon nanotubes to mercapto-containing silane coupling agent is 1:(10-20).
[0030] Preferably, the diameter of the sulfonated carbon nanotube is 30nm-70nm; further preferably, the diameter of the sulfonated carbon nanotube is 40nm-60nm.
[0031] Preferably, the thickness of the composite proton exchange membrane is 80 μm-120 μm; further preferably, the thickness of the composite proton exchange membrane is 90 μm-110 μm.
[0032] Preferably, the methanol permeability of the composite proton exchange membrane is 2.3×10 -7 cm 2 s -1 -6.3×10 -7 cm 2 s -1 ; Further preferably, the methanol permeability of the composite proton exchange membrane is 2.34×10 -7 cm 2 s -1 -6.25×10 -7 cm 2 s -1 .
[0033] Preferably, the proton conductivity of the composite proton exchange membrane at 25°C is 0.037 mScm -1 -0.057mScm -1 .
[0034] Preferably, the proton conductivity of the composite proton exchange membrane at 40°C is 0.052 mScm -1 -0.089mScm -1 .
[0035] Preferably, the proton conductivity of the composite proton exchange membrane at 60°C is 0.12 mScm -1 -0.18mScm -1 .
[0036] Preferably, the swelling rate of the composite proton exchange membrane at 25° C. is 8%-11.1%.
[0037] Preferably, the swelling rate of the composite proton exchange membrane at 60° C. is 13%-16%.
[0038] The second aspect of the present invention provides a method for preparing the composite proton exchange membrane according to the first aspect of the present invention, comprising the following steps:
[0039] The sulfonated polyetheretherketone, the sulfonated ZIF-derived porous carbon material and the sulfonated carbon nanotubes are mixed and dried to obtain the composite proton exchange membrane.
[0040] Preferably, the solvent in the mixing step includes at least one of dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, and N,N-dimethylacetamide; further preferably, the solvent in the mixing step includes at least one of N,N-dimethylformamide and N,N-dimethylacetamide.
[0041] Preferably, the drying step includes primary drying and secondary drying.
[0042] Preferably, the primary drying temperature is 60°C-80°C.
[0043] Preferably, the primary drying time is 6h-24h.
[0044] Preferably, the secondary drying temperature is 90°C-150°C.
[0045] Preferably, the secondary drying time is 6h-24h.
[0046] The third aspect of the present invention provides use of the composite proton exchange membrane according to the first aspect of the present invention in a fuel cell.
[0047] The beneficial effects of the present invention are:
[0048] Advantages and beneficial effects of the present invention:
[0049] The composite proton exchange membrane provided by the present invention has the advantages of low methanol permeability, low swelling rate and high proton conductivity. By filling sulfonated ZIF-derived porous carbon material and sulfonated carbon nanotubes, the proton conductivity of the composite proton exchange membrane can be improved, and the penetration of fuel can be blocked at the same time. The present invention overcomes the disadvantage of zinc-based ZIF being unstable in an acidic environment by carbonizing the zinc-based ZIF, making it suitable for preparing the composite proton exchange membrane. The preparation method of the composite proton exchange membrane is simple, efficient, low-cost, and has the advantage of being industrially producible. The composite proton exchange membrane can be widely used in fuel cells.
[0050] Specifically, the present invention has the following advantages:
[0051] 1. The sulfonated ZIF-derived porous carbon material filled in the composite proton exchange membrane disclosed in the present invention can greatly improve the proton conductivity of the composite membrane, and solve the problem of instability of the ZIF material in an acidic environment; the sulfonated carbon nanotube is an ideal filler that can not only significantly improve the mechanical stability and proton conductivity of the composite membrane, but also effectively inhibit the methanol permeation of the proton exchange membrane; when the sulfonated carbon nanotube and the sulfonated ZIF-derived porous carbon material are filled into the SPEEK matrix together, an efficient proton transport network can be established inside the composite proton exchange membrane, thereby improving the proton conductivity of the composite membrane and blocking the permeation of fuel, effectively solving the problems of low proton conductivity and high methanol permeability of the pure SPEEK membrane.
[0052] 2. The sulfonated polyetheretherketone used in the present invention as the matrix of the proton exchange membrane has the advantages of low cost and simple synthesis; the zinc-based ZIF used in the present invention has a uniform particle size, and the particle size is controllable. The prepared ZIF-derived porous carbon material has the advantages of uniform particle size, large specific surface area, and easy functionalization; by carbonizing the zinc-based ZIF, the disadvantage of its instability in an acidic environment is overcome, and it is suitable for the preparation of a composite proton exchange membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 The figure is a flow chart for the preparation of sulfonated polyetheretherketone.
[0054] Figure 2 The flowchart of the preparation of sulfonated carbon nanotubes.
[0055] Figure 3 Flow chart for the preparation of sulfonated ZIF-derived porous carbon materials.
[0056] Figure 4 This is the hydrogen nuclear magnetic resonance spectrum of sulfonated polyetheretherketone.
[0057] Figure 5 SEM image of sulfonated ZIF-derived porous carbon material.
[0058] Figure 6 This is the SEM image of sulfonated carbon nanotubes.
[0059] Figure 7 This is the SEM image of the surface of the composite proton exchange membrane prepared in Example 5.
[0060] Figure 8 This is a high-magnification SEM image of the cross-section of the composite proton exchange membrane prepared in Example 5.
[0061] Fig. 9 This is a cross-sectional SEM image of the composite proton exchange membrane prepared in Example 5.
[0062] Fig.10This is a physical photograph of the composite proton exchange membrane prepared in Example 5. DETAILED DESCRIPTION
[0063] The specific implementation of the present invention is further described below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.
[0064] The preparation steps of sulfonated polyetheretherketone are as follows: polyetheretherketone (PEEK) (molecular weight: 4000-21800) is placed in a vacuum oven and dried at 80°C for 24 hours. Assemble the reaction bottle in a water bath, add 100mL of 98% concentrated sulfuric acid, and then dissolve 5g of dried PEEK in concentrated sulfuric acid under stirring. React for 3 hours at 50°C with vigorous stirring. Prepare a large amount of ice-water mixture in advance, and after the reaction is completed, slowly pour the sulfuric acid solution of sulfonated polyetheretherketone (SPEEK) into ice water under mechanical stirring and draw it into filaments. Wash with pure water several times until neutral, collect SPEEK by filtration, and finally place in an oven and dry at 60°C for 24 hours to obtain a sulfonated polyetheretherketone with a sulfonation degree of 50%-80% (the sulfonation degree is obtained according to published literature). Figure 1 The figure is a flow chart for the preparation of sulfonated polyetheretherketone.
[0065] The preparation steps of sulfonated carbon nanotubes are as follows: carbon nanotubes with a diameter of 40nm-60nm are added to a mixed solution of concentrated sulfuric acid and concentrated nitric acid, and carboxylated carbon nanotubes are obtained after acidification at 80℃-100℃ for 4-6 hours. The above-mentioned carboxylated carbon nanotubes are mixed with toluene and 3-mercaptopropyltrimethoxysilane at a ratio of 1:70:15. The resulting mixture is refluxed at 80℃-120℃ for 2-24 hours. After the reaction, mercaptosilane-grafted CNTs (CNTs-SH) are obtained by filtration. The sulfhydryl (-SH) functional group of CNTs-SH is oxidized to sulfonate (-SO3H) using hydrogen peroxide (H2O2) solution as an oxidant to obtain sulfonated carbon nanotubes (SCNTs). Figure 2 Flow chart of the preparation of sulfonated carbon nanotubes.
[0066] The preparation steps of sulfonated ZIF-derived porous carbon material (C-ZIF-SO3H) are as follows:
[0067] 1) Preparation of zinc-based ZIF: Dissolve dimethylimidazole and zinc nitrate hexahydrate in 100mL-150mL of methanol respectively. After complete dissolution, quickly pour the methanol solution containing dimethylimidazole into the zinc nitrate solution under stirring. The resulting mixed solution is vigorously stirred for 5 minutes to 10 minutes and then allowed to stand for 1-2 hours. After the reaction is completed, the product is separated by a centrifuge and washed with methanol. The above product is placed in an oven at 60°C-100°C and dried to obtain a zinc-based ZIF material (ZIF-8).
[0068] 2) Preparation of ZIF-derived porous carbon material: The obtained zinc-based ZIF material (ZIF-8) was placed in a tubular furnace and calcined at 800° C.-1000° C. for 2-4 hours under a nitrogen atmosphere to obtain a ZIF-derived carbon material (C-ZIF).
[0069] 3) Preparation of sulfonated ZIF-derived porous carbon material (C-ZIF-SO3H): The ZIF-derived carbon material (C-ZIF) obtained above was mixed with toluene and 3-mercaptopropyltrimethoxysilane in a mass ratio of 1:70:15. A uniform mixed solution was prepared under ultrasound. The resulting mixed solution was transferred to a condensation reflux reaction device. Heat to 80°C and reflux for 4 hours. After the reaction was completed, the product was collected by filtration and washed several times with anhydrous ethanol to remove residual silane. The product was mercaptosilane-grafted C-ZIF (C-ZIF-SH). The collected C-ZIF-SH was dispersed in a 30% concentration H2O2 solution under ultrasound and reacted at room temperature for 5 hours under stirring. H2O2 solution was used as an oxidant to oxidize the -SH functional group in C-ZIF-SH to sulfonate (-SO3H) to obtain a sulfonated ZIF-derived porous carbon material (C-ZIF-SO3H). The product was obtained by filtration, washed and filtered with ethanol and water multiple times, and finally dried in an oven for later use. Figure 3 Flow chart for the preparation of sulfonated ZIF-derived porous carbon materials.
[0070] Example 1
[0071] The preparation steps of the composite proton exchange membrane in this example are as follows:
[0072] 1) First, prepare a N,N-dimethylacetamide (DMAC) solution of SPEEK. Dissolve the prepared SPEEK in the DMAC solution. Dissolve each gram of SPEEK in 10 mL of the DMAC solution.
[0073] 2) With the assistance of ultrasound, C-ZIF-SO3H was dispersed in the DMAC solution to form a uniform mixture. 10 mL of DMAC solution was used for every 100 mg of C-ZIF-SO3H.
[0074] 3) Take the SPEEK solution and C-ZIF-SO3H dispersion obtained above and mix them under stirring, and further mix them evenly under ultrasonic action. The mass ratio of SPEEK and C-ZIF-SO3H is 99:1. After obtaining a uniform solution, cast it on a glass plate and use a vacuum oven to continuously dry it at 80°C for 12 hours. Then, the membrane is further dried at 100°C for 12 hours to further remove the residual DMAC solution. Finally, a SPEEK composite proton exchange membrane with a filling mass percentage of 1.0% C-ZIF-SO3H is obtained, which is recorded as C-ZIF-SO3H_1.0wt.%@SPEEK. The thickness of the membrane is about 100μm.
[0075] Example 2
[0076] The preparation steps of the composite proton exchange membrane in this example are as follows:
[0077] 1) First, prepare a N,N-dimethylacetamide (DMAC) solution of SPEEK. Dissolve the prepared SPEEK in the DMAC solution. Dissolve each gram of SPEEK in 10 mL of the DMAC solution.
[0078] 2) With the assistance of ultrasound, C-ZIF-SO3H was dispersed in the DMAC solution to form a uniform mixture. 10 mL of DMAC solution was used for every 100 mg of C-ZIF-SO3H.
[0079] 3) Take the SPEEK solution and C-ZIF-SO3H dispersion obtained above and mix them under stirring, and further mix them evenly under ultrasonic action. The mass ratio of SPEEK and C-ZIF-SO3H is 97:3. After obtaining a uniform solution, cast it on a glass plate and use a vacuum oven to continuously dry it at 80°C for 12h. Then, the membrane is further dried at 100°C for 12h to further remove the residual DMAC solution. Finally, a SPEEK composite proton exchange membrane with a filling mass percentage of 3.0% C-ZIF-SO3H is obtained, which is recorded as C-ZIF-SO3H_3.0wt.%@SPEEK. The thickness of the membrane is about 100μm.
[0080] Example 3
[0081] The preparation steps of the composite proton exchange membrane in this example are as follows:
[0082] 1) First, prepare a N,N-dimethylacetamide (DMAC) solution of SPEEK. Dissolve the prepared SPEEK in the DMAC solution. Dissolve each gram of SPEEK in 10 mL of the DMAC solution.
[0083] 2) With the assistance of ultrasound, C-ZIF-SO3H was dispersed in the DMAC solution to form a uniform mixture. 10 mL of DMAC solution was used for every 100 mg of C-ZIF-SO3H.
[0084] 3) Take the SPEEK solution and C-ZIF-SO3H dispersion obtained above and mix them under stirring, and further mix them evenly under ultrasonic action. The mass ratio of SPEEK and C-ZIF-SO3H is 95:5. After obtaining a uniform solution, cast it on a glass plate and use a vacuum oven to continuously dry it at 80°C for 12 hours. Then, the membrane is further dried at 100°C for 12 hours to further remove the residual DMAC solution. Finally, a SPEEK composite proton exchange membrane with a filling mass percentage of 5.0% C-ZIF-SO3H is obtained, which is recorded as C-ZIF-SO3H_5.0wt.%@SPEEK. The thickness of the membrane is about 100μm.
[0085] Example 4
[0086] The preparation steps of the composite proton exchange membrane in this example are as follows:
[0087] 1) First, prepare a N,N-dimethylacetamide (DMAC) solution of SPEEK. Dissolve the prepared SPEEK in the DMAC solution. Dissolve each gram of SPEEK in 10 mL of the DMAC solution.
[0088] 2) With the assistance of ultrasound, C-ZIF-SO3H was dispersed in the DMAC solution to form a uniform mixture. 10 mL of DMAC solution was used for every 100 mg of C-ZIF-SO3H.
[0089] 3) Take the SPEEK solution and C-ZIF-SO3H dispersion obtained above and mix them under stirring, and further mix them evenly under ultrasonic action. The mass ratio of SPEEK and C-ZIF-SO3H is 93:7. After obtaining a uniform solution, cast it on a glass plate and use a vacuum oven to continuously dry it at 80°C for 12h. Then, the membrane is further dried at 100°C for 12h to further remove the residual DMAC solution. Finally, a SPEEK composite proton exchange membrane with a filling mass percentage of 7.0% C-ZIF-SO3H is obtained, which is recorded as C-ZIF-SO3H_7.0wt.%@SPEEK. The thickness of the membrane is about 100μm.
[0090] Example 5
[0091] The preparation steps of the composite proton exchange membrane in this example are as follows:
[0092] 1) First, prepare a N,N-dimethylacetamide (DMAC) solution of SPEEK. Dissolve the prepared SPEEK in the DMAC solution. Dissolve each gram of SPEEK in 10 mL of the DMAC solution.
[0093] 2) With the assistance of ultrasound, C-ZIF-SO3H was dispersed in the DMAC solution to form a uniform mixture. 10 mL of DMAC solution was used for every 100 mg of C-ZIF-SO3H.
[0094] 3) With the assistance of ultrasound, SCNTs were dispersed in DMAC solution to form a uniform mixture, using 10 mL of DMAC solution for every 100 mg of SCNTs.
[0095] 4) Take the SPEEK solution obtained above, mix the C-ZIF-SO3H dispersion and the SCNTs dispersion under stirring, and further mix them evenly under ultrasonic action. The mass ratio of SPEEK, C-ZIF-SO3H and SCNTs is 96.5:3:0.5. After obtaining a uniform solution, cast it on a glass plate and use a vacuum oven to continuously dry it at 80°C for 12h. Then, the membrane is further dried at 100°C for 12h to further remove the residual DMAC solution. Finally, a co-filled SPEEK composite proton exchange membrane with a mass percentage of 3.0% C-ZIF-SO3H and a mass percentage of 3.0% SCNTs is obtained, which is recorded as C-ZIF-SO3H_3.0wt.% / SCNTs_0.5wt.%@SPEEK. The thickness of the membrane is about 100μm.
[0096] Example 6
[0097] In the preparation steps of the composite proton exchange membrane of this example, the mass ratio of SPEEK, C-ZIF-SO3H and SCNTs is 96:3:1 respectively, and the remaining steps are the same as those of Example 5. The prepared composite proton exchange membrane is named C-ZIF-SO3H_3.0wt.% / SCNTs_1wt.%@SPEEK.
[0098] Example 7
[0099] In the preparation steps of the composite proton exchange membrane of this example, the mass ratio of SPEEK, C-ZIF-SO3H and SCNTs is 94:3:3, respectively, and the remaining steps are the same as those of Example 5. The prepared composite proton exchange membrane is named C-ZIF-SO3H_3.0wt.% / SCNTs_3wt.%@SPEEK.
[0100] Example 8
[0101] In the preparation steps of the composite proton exchange membrane of this example, the mass ratios of SPEEK, C-ZIF-SO3H and SCNTs are 92:3:5 respectively, and the remaining steps are the same as those of Example 5. The prepared composite proton exchange membrane is named C-ZIF-SO3H_3.0wt.% / SCNTs_5wt.%@SPEEK.
[0102] Comparative Example 1
[0103] The preparation steps of the composite proton exchange membrane in this example are as follows:
[0104] 1) First, prepare a N,N-dimethylacetamide (DMAC) solution of SPEEK. Dissolve the prepared SPEEK in the DMAC solution. Dissolve each gram of SPEEK in 10 mL of the DMAC solution.
[0105] 2) The SPEEK solution obtained above was cast onto a glass plate and dried continuously at 80°C for 12 hours in a vacuum oven. Then, the membrane was further dried at 100°C for 12 hours to further remove the residual DMAC solution. Finally, a SPEEK proton exchange membrane was obtained, which was denoted as SPEEK. The thickness of the membrane was about 100 μm.
[0106] Performance Testing
[0107] The prepared sulfonated polyetheretherketone was subjected to nuclear magnetic resonance hydrogen spectrum test. Figure 4 This is the H NMR spectrum of sulfonated polyetheretherketone. Figure 4 It can be seen that the sulfonated polyetheretherketone structure prepared in the embodiment is as follows;
[0108]
[0109] The prepared sulfonated ZIF-derived porous carbon material was tested by scanning electron microscopy. Figure 5 The SEM image of sulfonated ZIF-derived porous carbon material. Figure 5 It can be seen that the particle size of the sulfonated ZIF-derived porous carbon material is 80nm-200nm. The prepared sulfonated carbon nanotubes were tested by scanning electron microscopy. Figure 6 This is the SEM image of sulfonated carbon nanotubes.
[0110] Figure 7 This is the SEM image of the surface of the composite proton exchange membrane prepared in Example 5. Figure 8 This is a high-magnification SEM image of the cross-section of the composite proton exchange membrane prepared in Example 5. Fig. 9 This is a cross-sectional SEM image of the composite proton exchange membrane prepared in Example 5. Fig.10 This is a photo of the composite proton exchange membrane prepared in Example 5. Fig. 9 It can be seen that the thickness of the composite proton exchange membrane is 99 μm.
[0111] The composite proton exchange membranes prepared in Examples 1-8 and Comparative Example 1 were tested for ion exchange capacity, water absorption and swelling rate, electrical conductivity and methanol permeability. The test methods for water absorption (WU%), swelling rate (SR%), ion exchange capacity (IEC), electrical conductivity and methanol permeability are as follows:
[0112] Water absorption refers to the percentage of the difference in mass between the fully wet and dry membrane materials to the mass of the dry membrane material. Place the acid polymer membrane in distilled water and soak it at a set temperature for 24 hours. When the water absorption and water desorption rate of the membrane material reach equilibrium, quickly wipe off the water on the membrane surface and weigh it. Repeat the experiment 3 to 5 times until the weight is a constant and take the average value as W. w Finally, it was placed in a vacuum oven and dried at 100°C for 24 hours and weighed to obtain W d The water absorption value can be obtained by formula (1).
[0113]
[0114] In formula (1): W d Indicates the dry film weight (g), W w Indicates the weight of the film in wet state (g).
[0115] The swelling rate test is to soak the acid polymer membrane in deionized water at a set temperature for 24 hours. When the water absorption rate and water desorption rate of the membrane material reach equilibrium, the water on the membrane surface is quickly wiped off and the membrane size is measured. The experiment is repeated 3 to 5 times until the membrane size is a constant. The membrane is then placed in a vacuum oven and dried at 100°C for 24 hours before measuring the membrane size. The swelling rate value can be obtained by formula (2).
[0116]
[0117] In formula (2), L w and L d The dimensions of the membrane in the fully wet state and the fully dry state (cm) are shown respectively.
[0118] The ion exchange capacity reflects the density of proton groups in the proton exchange membrane, which is also one of the important indicators of the proton conductivity of the reaction membrane. The IEC of the membrane can be determined by acid-base titration. The pretreated proton exchange membrane is placed in a weighing bottle and dried in a vacuum oven to constant weight, and then accurately weighed with an analytical balance. The dry weight of the membrane to be tested is 0.0447 W / m2. The plasma polymerized proton exchange membrane is immersed in 50 mL of saturated NaCl solution for 48 hours to make the H in the membrane +All are replaced. Take out the membrane and rinse it with deionized water for 3 times. Pour the rinse water into the original NaCl solution. Then use phenolphthalein as an indicator and titrate it with a pre-calibrated NaOH solution of about 0.01 mol / L until it turns pink. Use phenolphthalein as an indicator. The calculated value of ion exchange capacity (IEC) can be obtained by formula (3).
[0119]
[0120] Among them, C NaOH is the concentration of NaOH solution (mol / L); V NaOH is the volume of NaOH solution consumed (mL); W d is the mass of dry proton exchange membrane (g).
[0121] Proton conductivity is the most important parameter for the performance of the reaction membrane. The proton conductivity test of the proton exchange membrane adopts the three-electrode AC impedance test method. In this test, the Solatron 1260 electrochemical workstation was used to test and analyze the proton conductivity of the membrane material in the horizontal direction. First, the membrane was cut into long strips (such as 1cm×5cm), and the working electrode (WC) and the auxiliary electrode (CE) were connected at both ends of the length direction. The reference electrode (RE) was connected to the center of the membrane to measure the impedance of the membrane in the horizontal direction. The impedance spectrum of the membrane was measured at a frequency of 1MHz to 100MHz and an amplitude of 10mV, and the resistance value of the membrane was obtained by fitting. According to the membrane resistance (R res ), the distance between the working electrode and the counter electrode (d) and the cross-sectional area (S) of the membrane are calculated by formula (4) to obtain the proton conductivity of the membrane.
[0122]
[0123] Methanol permeability (P) is one of the key parameters affecting membrane performance. The methanol permeability of the composite membrane was tested using a three-electrode system of an electrochemical workstation (Shanghai CHI-760E), with Pt sheet, saturated Ag / AgCl and Pt / C gas diffusion electrode as the auxiliary electrode, reference electrode and working electrode. The membrane to be tested was placed between the supply chamber and the receptor chamber and fixed and sealed by a rubber ring. The active area of the membrane to be tested was approximately 1.70 cm 2 . A solution consisting of 10vt.% methanol and 0.5mol / LH2SO4 was fed into the donor chamber, and 0.5mol / L H2SO4 was fed into the acceptor chamber with the same volume of solution. During the experiment, the solutions in the two chambers were constantly stirred, and pure O2 passed steadily and continuously near the working electrode. The permeation of methanol in the membrane is caused by the difference in methanol concentration on both sides, which causes the potential of the working electrode to drop. The methanol concentration in the acceptor chamber can then be determined based on the calibration curve. Methanol permeability P (cm2 / s) is calculated according to equation (5).
[0124]
[0125] Where S represents the permeation active area of the membrane, C A and C B represents the methanol concentration in the donor compartment and the acceptor compartment, V B represents the volume of the solution in the receptor compartment, and D represents the diffusion coefficient of methanol.
[0126] Table 1 shows the test data of ion exchange capacity, water absorption rate and swelling rate of the composite proton exchange membrane.
[0127] Table 1 Test results of ion exchange capacity, water absorption and swelling rate of composite proton exchange membrane
[0128]
[0129] According to Table 1, when C-ZIF-SO3H is filled into the SPEEK matrix, the water absorption and swelling rate of the C-ZIF-SO3H@SPEEK membrane show a downward trend with the increase of the filling amount. This is because the presence of inorganic particles occupies the free space in the membrane and the interaction with the organic polymer matrix restricts the free movement of the SPEEK molecular chain, thereby reducing the swelling rate and water absorption rate of the composite membrane. This is conducive to improving the structural stability of the composite membrane under high temperature and high humidity environment. When SCNTs are further added on the basis of further filling C-ZIF-SO3H, the water absorption and swelling rate of the composite membrane further decrease with the increase of the SCNTs filler content. This is also because more inorganic particles are introduced into the membrane to occupy more free space in the membrane and restrict the free movement of SPEEK polymers, which is conducive to increasing the structural stability of the composite membrane under high temperature and high humidity environment. Whether it is C-ZIF-SO3H or SCNTs, the IEC of the composite membrane shows a downward trend with the increase of the filler filling amount. This is because the filled inorganic particles dilute the local density of the sulfonic acid groups in the composite membrane.
[0130] Table 2 shows the test data of the conductivity and methanol permeability of the composite proton exchange membrane.
[0131] Table 2 Test results of conductivity and methanol permeability of composite proton exchange membrane
[0132]
[0133] According to Table 2, with the increase of C-ZIF-SO3H filling amount, the proton conductivity of C-ZIF-SO3H@SPEEK membrane shows a trend of first rising and then falling, and when the filling amount is 3.0wt.%, the proton conductivity of C-ZIF-SO3H@SPEEK membrane reaches the maximum value, which is much higher than that of pure SPEEK membrane. In the SPEEK matrix, an appropriate amount of C-ZIF-SO3H (≤3.0wt.%) can reduce the swelling rate of the membrane, shorten the spacing between the sulfonic acid groups, and more easily form continuous hydrophilic ion clusters in the membrane water absorption state, which creates conditions for the construction of continuous proton transport channels in the membrane. In addition, the rich pore structure of C-ZIF-SO3H itself and the hydrophilic sulfonic acid groups on its surface are also conducive to the construction of additional proton transport channels, thereby improving the proton conductivity of C-ZIF-SO3H@SPEEK membrane. The methanol permeability of C-ZIF-SO3H@SPEEK membrane follows the rule of C-ZIF-SO3H filling amount, which is first decreased and then increased, and reaches the minimum value when the filling amount reaches 3.0wt.%, which is slightly lower than SPEEK membrane. This is because the dense C-ZIF-SO3H filler blocks the channel for methanol permeation relative to SPEEK, thereby inhibiting the methanol permeability of the composite membrane. When the membrane is filled with too much C-ZIF-SO3H (>3.0wt.%), the C-ZIF-SO3H in the membrane agglomerates, destroying the dense structure of the membrane, which is not conducive to forming an effective ion cluster structure with the sulfonic acid group of SPEEK, thereby reducing the proton conductivity of the composite membrane. When SCNTs are further filled on the basis of filling 3.0wt.% C-ZIF-SO3H, the proton conductivity of the composite membrane first increases and then decreases with the increase of SCNTs filling amount, and reaches the maximum value when the filling amount reaches 0.5wt.%. But at the same time, the methanol permeability of the composite membrane dropped significantly and reached the lowest value when the filling amount was 3.0wt.%, which was much lower than that of the SPEEK membrane. This shows that the filling of C-ZIF-SO3H and SCNTs can establish an efficient proton transport network in SPEEK, thereby greatly improving the proton conductivity of the composite membrane. At the same time, the combination of C-ZIF-SO3H particles and SCNTs can also effectively block the penetration of methanol, thereby greatly reducing the methanol permeability of the composite membrane. According to the above results, it can be seen that the best embodiment of the present invention is the C-ZIF-SO3H-3.0wt.% / SCNTs-0.5wt.%@SPEEK membrane of Example 5.
[0134] The mass ratio of C-ZIF to toluene and 3-mercaptopropyltrimethoxysilane in the above embodiment should not be limited to the above 1:70:15, but can be other ratios, and the thiolated ZIF-derived porous carbon material can also be obtained. The toluene solvent used can also be replaced by other organic solvents such as ethanol, and should not be construed as being limited to toluene.
[0135] The concentration of the concentrated hydrogen peroxide solution used in the above embodiment is not limited to 30%, and concentrated hydrogen peroxide solutions of other concentrations may also be used.
[0136] The solvent used in the preparation of the SPEEK composite proton exchange membrane in the above embodiment is not limited to N,N-dimethylacetamide, and may also be replaced by an organic solvent such as N,N-dimethylformamide or dimethyl sulfoxide that can dissolve SPEEK.
[0137] The above examples are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above examples. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A composite proton exchange membrane, characterized in that: The composite proton exchange membrane comprises a matrix and a filler; the matrix comprises sulfonated polyetheretherketone; the filler comprises sulfonated ZIF-derived porous carbon material and sulfonated carbon nanotubes; The mass ratio of the sulfonated polyetheretherketone, the sulfonated ZIF-derived porous carbon material and the sulfonated carbon nanotube is (20-35):1:(0.1-3); The sulfonated ZIF-derived porous carbon material is prepared by a preparation method comprising the following steps: 1) mixing dimethylimidazole and zinc salt, reacting to obtain a zinc-based ZIF material; 2) calcining the zinc-based ZIF material in an inert atmosphere or under vacuum to obtain a ZIF-derived porous carbon material; 3) mixing the ZIF-derived porous carbon material with a mercapto-containing silane coupling agent to obtain a mercaptosilane-grafted ZIF-derived porous carbon material; 4) oxidizing the mercaptosilane-grafted ZIF-derived porous carbon material to obtain the sulfonated ZIF-derived porous carbon material; The sulfonated carbon nanotubes are prepared by a preparation method comprising the following steps: a) oxidizing the carbon nanotubes to obtain carboxylated carbon nanotubes; b) mixing the carboxylated carbon nanotubes with a mercapto-containing silane coupling agent to obtain mercaptosilane-grafted carbon nanotubes; c) oxidizing the carbon nanotubes grafted with mercaptosilane to obtain the sulfonated carbon nanotubes.
2. The composite proton exchange membrane according to claim 1, characterized in that: The sulfonated polyetheretherketone contains a repeating unit as shown in formula (I); (Ⅰ); In formula (I), x is selected from a positive integer of 5-50, y is selected from a positive integer of 20-60, and y / x is selected from a positive integer of 0.8-5.
3. The composite proton exchange membrane according to claim 1, characterized in that: In the step 3), the mass ratio of the ZIF-derived porous carbon material to the mercapto-containing silane coupling agent is 1:(10-30).
4. The composite proton exchange membrane according to claim 1, characterized in that: In the step b), the mass ratio of the carboxylated carbon nanotubes to the mercapto-containing silane coupling agent is 1:(5-25).
5. The composite proton exchange membrane according to any one of claims 1 to 4, characterized in that: The thickness of the composite proton exchange membrane is 80 μm-120 μm.
6. The method for preparing the composite proton exchange membrane according to any one of claims 1 to 5, characterized in that: The following steps are involved: The sulfonated polyetheretherketone, the sulfonated ZIF-derived porous carbon material and the sulfonated carbon nanotubes are mixed and dried to obtain the composite proton exchange membrane.
7. Use of the composite proton exchange membrane according to any one of claims 1 to 5 in a fuel cell.
Citation Information
Patent Citations
Proton exchange membrane and preparation method and application thereof
CN113506904A